Tinjauan Kritis Terhadap Efektivitas Penegakan Etika dan Tanggung Jawab Profesi Hukum - Amelia, Sabina Putri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Enforcing ethics and responsibility in the legal profession is a fundamental element in maintaining the legitimacy of the legal system and public trust. This article critically examines how the mechanism of supervision and implementation of disciplinary sanctions against violators of legal professional ethics contributes to increasing the responsibility and integrity of the profession as a whole. Using normative legal research methods, this study analyzes legal norms, codes of ethics, and the role of supervisory institutions such as the Honorary Council, the Judicial Commission, and the Prosecutorial Commission. The findings show that sanctions that are applied consistently and proportionally function not only as a form of punishment, but also as an educational, preventive, and restorative tool. Effective implementation of sanctions can encourage ethical awareness among legal professionals, strengthen internal accountability, and restore public trust. However, this effectiveness is still hampered by factors such as weak institutional independence, procedural uncertainty, and low ethical culture. Therefore, structural reform and continuous ethics education are needed to build a dignified and integrity-based legal profession.